Relationship Between Social Relationships Quality, Emotional Intelligence, and Work Environment to Psychological Well-Being - Roellyanti, Maria Valeria (Relevance: Journal of Management and Business, 2024)
This study used a quantitative approach with a cross sectional design. The aim was to explore the relationship between the quality of social relationships, emotional intelligence, and work environment and psychological well-being. A total of 145 respondents who actively worked from various sectors or industries were selected through the purposive sampling method. The research instrument was a questionnaire with five Likert scales 1-5.  Data collection will be conducted from December 15, 2023 to January 15, 2024. The data was analyzed using Structural Equation Modeling (SEM) with the help of AMOS software. Path analysis is used to test the relationship between the variables studied, while the validity and reliability of the instrument are examined through factor analysis. The results showed that the quality of good social relationships, high levels of emotional intelligence, and a supportive work environment have a strong and positive influence on the psychological well-being of working individuals. This research makes an important contribution in deepening our understanding of how the interaction between these factors together affects psychological well-being. With a deeper understanding of these dynamics, it is expected to develop strategies that are more effective in improving the quality of the work environment and psychological well-being of employees. Therefore, the results of this study not only provide empirical findings on the relationship between these variables, but also have the potential to be the basis for the development of policies and management practices that are more oriented towards employee welfare. By adjusting the work environment and paying greater attention to aspects such as the quality of social relationships and the building of emotional intelligence, organizations can strengthen the psychological well-being of their employees. This not only means improving an individual's working life, but also having a wider positive impact on productivity and overall work quality.